The David Sign, Revisited - Daniel M. Gelfman, MD (American Journal of Medicine Open, 2024)
This commentary discusses a new, previously unrecognized, undocumented, anatomic finding concerning the jugular venous distention present on one of the world’s most famous statues, Michelangelo’s David. This finding is provocative as it involves of one of Michelangelo’s “messages” being demonstrated in The David, has clinical relevance, and, appears to reveal something about Michelangelo, himself.